Biomimetic Locomotion on Water of a Porous Natural Polymeric Composite. Issue 11 (4th March 2016) - Liakos, Ioannis L.; Salvagnini, Pietro; Scarpellini, Alice; Carzino, Riccardo; Beltran, Carlos; Mele, Elisa; Murino, Vittorio; Athanassiou, Athanassia
Abstract : Observation of the natural world can provide invaluable information on the mechanisms that semi‐aquatic living organisms or bacteria use for their self‐propulsion. Microvelia, for example, uses wax excreted from its legs to move on water in order to escape from predators or reach the bank of the river. Mimicking such mechanism, few self‐propelled materials on water, as camphor, have been previously developed, but weak points like slow locomotion, short movement duration, or shape restrictions still need to be improved. This study presents a totally green self‐assembled porous system, formed by the combination of a natural polymer with an essential oil that spontaneously moves on water for hours upon expulsion of the oil, with high velocities reaching 15 cm s −1 . The structural characteristics of the natural polymeric composite are carefully analyzed and associated to its spontaneous movement. Surface tension experiments are also presented that connect the essential oil release with the locomotion of the porous composite films. This research work opens novel routes toward bioinspired natural materials that can be used for mimicking and studying the motion of bioorganisms and microorganisms, and for applications such as energy harvesting, aquatic pollution monitoring, drug delivery, to name few. Abstract : Essential oils are encapsulated into cellulose acetate and porous films with self‐motor properties on air/water interface are created. The essential oil is slowly released on water leading to a surface tension gradient between the region in the vicinity of the film and away from it. This gradient can drive the motion for 3 h reaching velocities higher than 10 cm s −1 .